Distributed Fault Estimation of Nonlinear Networked Systems: Application to Robotic Manipulator. (12th August 2014) - Chen, Juntong; Ling, Rongyao; Ni, Hongjie; Zhang, Dan
Abstract : This paper is concerned with the distributed fault estimation for a class of nonlinear networked systems, where the T-S fuzzy model is utilized to approximate the nonlinear plant and the whole fault estimation task is operated by a wireless sensor network. Due to the limited power in sensors, signal is quantized before transmission. Based on the Lyapunov stability theory and the robust control approach, a sufficient condition is obtained such that the estimation error system is asymptotic stable with a prescribed H ∞ performance level. Finally, a case study on the actuator fault estimation of robotic manipulator is given to show the effectiveness of the proposed design.